Understanding the interaction of upper respiratory tract infection with respiratory syncytial virus and Streptococcus pneumoniae using a human challenge model: a multicenter, randomized controlled study protocol - Sanjita Brito-Mutunayagam; David O. Hamilton; Elena Mitsi; Carla Solórzano; Grace Li; Bruno Rocha De Macedo; Filora Elterish; Xinxue Liu; Kiarash Tanha; Rachel White; Angela Hyder-Wright; Bhumika Patel; et al. (PLoS ONE, 2025)
Background Streptococcus pneumoniae (pneumococcus) and respiratory syncytial virus (RSV) are major causes of respiratory infections globally. Viral and bacterial co-infections are commonly observed in respiratory infections and there is evidence that these pathogens interact synergistically to evade host responses and lead to more severe disease. Notably, RSV seasonal outbreaks are associated with increased hospitalization and a subsequent peak in invasive pneumococcal disease cases, particularly in pediatric populations. Here, we summarize a protocol for a controlled human infection model aiming to evaluate pathogen interaction dynamics and immune responses in a combined pneumococcus and RSV model. The primary objective is to determine whether primary RSV challenge increases the risk of secondary pneumococcal colonization. Methods This is an open-label, multi-center, randomized controlled human co-infection study, inclusive of a pilot phase. Individuals will be randomized to primary inoculation with either pneumococcus (serotype 6B) or RSV (subtype RSV-A) intra-nasally on day 0 followed by a reciprocal challenge on day 7. During pilot phase A up to 10 participants will be monitored in an in-patient facility for 7–10 days following RSV-A challenge. If there are no safety concerns, we will then progress to an outpatient phase where participants will self-isolate at home. Clinical samples to be taken from participants include nasal swabs and washes for pathogen detection; and nasal cells, nasal lining fluid, and blood samples to examine mucosal and systemic immune responses. Discussion This work will lead to important scientific knowledge on the interaction and dynamics between pneumococcus and RSV. This knowledge could help inform pneumococcal and RSV vaccination strategies, particularly for groups at risk of developing severe pneumococcal and RSV disease. Trial registration The study is registered on ISRCTN (The UKs Clinical Study Registry). DOI https://doi.org/10.1186/ISRCTN12036902